Aggression by patients and their relatives against mental health nurses in the workplace - Gudonytė, Rūta; Palinauskienė, Liucija Ramunė (Slauga. Mokslas ir praktika, 2023)
Investigation problem. Violence in healthcare facilities has become a global phenomenon that requires immediate attention. The nursing profession is particularly affected, and the vulnerability of nurses to workplace violence is particularly evident in mental health nursing. Aggression at work is a big problem for both nurses and patients and their relatives. Communication with patients deteriorates, attention and concentration to solve the patient’s health problems decreases, the quality of life of the family and the nurse deteriorates, and the opportunity to improve. The purpose of the study is to evaluate the aggression of patients and relatives against mental health nurses in the workplace. Methodology of investigation. A quantitative study using an anonymous survey in online. Study participants 118 mental health nurses. Research results and conclusions. The most common types of aggression at work are verbal and physical, and the least common is sexual harassment. The main risk factors for aggression depended on patients and relatives, on the status and personal characteristics of the caregiver, and on the work environment. When nurses encountered an aggressor, they usually tried to calm him down by communicating, removing stimuli from the environment that promote aggression.